ANALISIS VALIDITAS PENGEMBANGAN MIWALL (MEDIA INTERAKTIF BERBASIS WORDWALL) UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SD - Kartika Ningsih; Ina Agustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the validity of the development of MIWALL (Wordwall-Based Interactive Media) as a learning media to improve the learning outcomes of fourth grade elementary school students in science. The method used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation instruments in the form of assessment sheets from material experts, media experts, and practitioners (teachers) are used to assess the quality of the media. The validation results show that MIWALL obtained an average score of 89% from all validators, which is included in the "very valid" category. These findings indicate that MIWALL is suitable for use as an interactive learning media in science subjects to increase student engagement and understanding of concepts in a fun way. The use of MIWALL is expected to be an innovative alternative in the thematic learning process in elementary schools